Practically useful protein-design methods combining phylogenetic and atomistic calculations. (August 2020) - Weinstein, Jonathan; Khersonsky, Olga; Fleishman, Sarel J
Highlights: Stability-threshold effects and biomolecular epistasis limit protein design. A deeper understanding of these limitations led to successful design methods. New design methods enable effective protein optimization without experimental iterations. Some design methods are available through web servers enabling non-expert users. Abstract : Our ability to design new or improved biomolecular activities depends on understanding the sequence-function relationships in proteins. The large size and fold complexity of most proteins, however, obscure these relationships, and protein-optimization methods continue to rely on laborious experimental iterations. Recently, a deeper understanding of the roles of stability-threshold effects and biomolecular epistasis in proteins has led to the development of hybrid methods that combine phylogenetic analysis with atomistic design calculations. These methods enable reliable and even single-step optimization of protein stability, expressibility, and activity in proteins that were considered outside the scope of computational design. Furthermore, ancestral-sequence reconstruction produces insights on missing links in the evolution of enzymes and binders that may be used in protein design. Through the combination of phylogenetic and atomistic calculations, the long-standing goal of general computational methods that can be universally applied to study and optimize proteins finally seems within reach.